Consumer Animosity and Boycott Dynamics in Emerging Markets: Quantitative Research from Egypt - Menna ABDELSHAFAY; Ahmed Yehia EBEID; Kenji YOKOYAMAand Mahmoud Mohamed FAWZY (Communications of International Proceedings, 2024)
This study investigates the influence of consumer animosity and attitudes on boycott intentions within the Egyptian context, where socio-political factors significantly shape consumer behavior. Given the rise of political tensions, understanding the psychological and behavioral mechanisms that drive consumer boycotts is critical. While previous research has explored animosity and consumer attitudes, a gap exists in examining how these factors interplay in politically sensitive markets like Egypt, where brands are often associated with foreign political stances. A survey-based methodology was employed, with factor analysis utilized to assess the relationships among the constructs of consumer animosity, attitude, and boycott intention. Data was analyzed using Partial Least Squares (PLS), confirming strong reliability and convergent validity of the measurement model. The study's findings reveal that animosity directly impacts both attitude (β = 0.592) and boycott intention (β = 0.233). Additionally, attitude plays a significant mediating role between animosity and boycott intention (β = 0.311), highlighting the critical role of consumer perceptions in politically charged environments. This study contributes to the literature by confirming that heightened animosity leads to stronger negative attitudes and increased boycott intention, offering actionable insights for businesses and policymakers. Given the findings, companies in politically sensitive markets should be mindful of local consumer sentiments, adopting transparent and culturally sensitive marketing strategies to mitigate the effects of animosity on brand perception.
Keywords: Consumer animosity; Boycott intention; Socio-political factors; Corporate social responsibility (CSR)